2008
DOI: 10.1248/cpb.56.802
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Nonbonded S...N Interaction in Rabeprazole

Abstract: Intramolecular nonbonded S · · · X (XϭS, O, N, etc.) interactions have been observed in a large number of organosulfur compounds controlling the conformation of small and large molecules. [1][2][3][4][5][6][7][8][9][10][11][12] Some of these compounds showed the strong bioactivity, and we suggested that the intramolecular nonbonded S · · · X interactions play an important role on the mechanism of several biological effects.1,2,6-12) For example, the clear S · · · O close contact in the complex crystalline str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…[167] Analytic energy gradient in the presence of multi-pole field was implemented in the Gaussian 03 code [168] to compute the higher derivatives. [169,170] The LAS were calculated for a grid of electrostatic multipole coefficients C by diagonalizing the local Hamiltonian operator expanded in a harmonic basis set. The ARNOLDI matrix diagonalization algorithm was employed in these vibrational configuration interactions (vibrational CI) calculations.…”
Section: Electrostatic Fluctuations Of the Local Hamiltonian Operatorsmentioning
confidence: 99%
“…[167] Analytic energy gradient in the presence of multi-pole field was implemented in the Gaussian 03 code [168] to compute the higher derivatives. [169,170] The LAS were calculated for a grid of electrostatic multipole coefficients C by diagonalizing the local Hamiltonian operator expanded in a harmonic basis set. The ARNOLDI matrix diagonalization algorithm was employed in these vibrational configuration interactions (vibrational CI) calculations.…”
Section: Electrostatic Fluctuations Of the Local Hamiltonian Operatorsmentioning
confidence: 99%
“…Hayashi et al have already suggested the existence of a N … S interaction in neutral rabeprazole, based on crystallographic distances. [23] These authors synthesized several derivatives of rabeprazole, which presented N … S distances around 0.27-0.28 nm ∇ 2 ρ envelope map of c5 in Fig. 3 can help to understand the N … S interaction.…”
Section: Conformational Analysis Of Timoprazolementioning
confidence: 99%
“…[167] Analytische Energiegradienten in Gegenwart von Multipolfeldern wurden auch in Gaussian 03 [168] implementiert, um höhere Ableitungen berechnen zu können. [169,170] Durch Diagonalisierung des in einen harmonischen Basissatz entwickelten lokalen Hamilton-Operators wurden die lokalen Amidzustände in einem Gitternetz von elektrostatischen Multipolkoeffizienten C ermittelt, wobei zur Berechnung der Schwingungskonfigurationswechselwirkung (Schwingungs-CI) der ARNOLDI-Algorithmus für die Matrixdiagonalisierung angewendet wurde. Die Übergangsschwingungsfrequenz vom Grundzustand in den LAS a und die Übergangsdipolmomente zwischen LAS a und b der mten Peptideinheit wurden quadratisch in C entwickelt [Gl.…”
Section: Angewandte Chemieunclassified